Retirement Forced Saving in Peru using Hyperbolic Discounting Functions: A Doctoral Research Proposal - Sanchez-Chavez, Dr Elio J. (Pontificia Universidad Católica del Perú. CENTRUM, 2008)
Empirical and survey data related to voluntary pensions in the United States indicated that households have not been saving enough to cover later consumption requirements. This evidence has been analyzed using a conceptual framework named the hyperbolic consumption model that integrates a classical utility theory with behavioral concepts in order to explain some anomalies in consumption-saving decisions.
Keywords: Consumption; Hyperbolic Functions; Pensions; Retirement; Saving; Time Preference; https://purl.org/pe-repo/ocde/ford#5.02.04